2017
DOI: 10.3892/mmr.2017.8101
|View full text |Cite
|
Sign up to set email alerts
|

miR‑455‑5p promotes cell invasion and migration in breast cancer

Abstract: MicroRNA (miR)‑455‑5p has been identified as a biomarker for various types of cancer and may therefore be involved in the regulation of cancer development and progression. However, the specific role and function of miR‑455‑5p in breast cancer remains unclear. The present study explored the expression levels and function of miR‑455‑5p in breast cancer. The results from reverse transcription‑quantitative polymerase chain reaction analysis revealed that miR‑455‑5p was significantly upregulated in breast cancer. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In this study, we also validated the molecular mechanism of gga-miR-455-5p of most interest based on our results, both present and past, and in relation to the data present in the literature. It has been demonstrated that gga-miR-455-5p played an important role in various cancers and virus [33][34][35][36]. For example, miR-455-5p had the ability to promote cell invasion and migration in breast cancer [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we also validated the molecular mechanism of gga-miR-455-5p of most interest based on our results, both present and past, and in relation to the data present in the literature. It has been demonstrated that gga-miR-455-5p played an important role in various cancers and virus [33][34][35][36]. For example, miR-455-5p had the ability to promote cell invasion and migration in breast cancer [35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that gga-miR-455-5p played an important role in various cancers and virus [33][34][35][36]. For example, miR-455-5p had the ability to promote cell invasion and migration in breast cancer [35]. In chickens, gga-miR-455-5p was downregulated in response to Newcastle disease virus (NDV) infection, and targeted SOCS3 to inhibit NDV replication [36].…”
Section: Discussionmentioning
confidence: 99%
“…High expressed miR-455-5p was an independent prognostic factor for poor survival for breast cancer patients. In vitro experiments showed overexpression of miR-455-5p accelerated invasiveness and migration capabilities of breast cancer cells [27]. Li et al also found that miR-455 was intensively overexpressed in TNBC tissue and Abbreviations: CDKN1B, cyclin dependent kinase inhibitor 1B; ER, estrogen receptor; HER2, human epidermal growth factor 2; PAM50, research-based 50-gene prediction analysis of a microarray; PR, progesterone receptor; SMAD4, SMAD family member 4.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous microRNAs (miRNAs) have been confirmed to exert a tumor‐promoting effect in BC. For instance, miR‐455‐5p is upregulated in BC and accelerates cell invasion and migration 14 . MiR‐146a enhances the proliferation and metastasis of BC cells by suppressing NM2‐H1 15 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, miR‐455‐5p is upregulated in BC and accelerates cell invasion and migration. 14 MiR‐146a enhances the proliferation and metastasis of BC cells by suppressing NM2‐H1. 15 Previous research has reported that miR‐513a‐5p often functions as an onco‐miR in diverse cancers.…”
Section: Introductionmentioning
confidence: 99%